SOX2 Expression Does Not Guarantee Cancer Stem Cell-like Characteristics in Lung Adenocarcinoma - Seung-Hyun Bae; Kyung Yong Lee; Suji Han; Chul Won Yun; ChanHyeok Park; Hyonchol Jang (Cells, 2024)
Effectively targeting cancer stemness is essential for successful cancer therapy. Recent studies have revealed that SOX2, a pluripotent stem cell factor, significantly contributes to cancer stem cell (CSC)-like characteristics closely associated with cancer malignancy. However, its contradictory impact on patient survival in specific cancer types, including lung adenocarcinoma (LUAD), underscores the need for more comprehensive research to clarify its functional effect on cancer stemness. In this study, we demonstrate that SOX2 is not universally required for the regulation of CSC-like properties in LUAD. We generated SOX2 knockouts in A549, H358, and HCC827 LUAD cells using the CRISPR/Cas9 system. Our results reveal unchanged CSC characteristics, including sustained proliferation, tumor sphere formation, invasion, migration, and therapy resistance, compared to normal cells. Conversely, SOX2 knockdown using conditional shRNA targeting SOX2, significantly reduced CSC traits. However, these loss-of-function effects were not rescued by SOX2 resistant to shRNA, underscoring the potential for SOX2 protein level-independent results in prior siRNA- or shRNA-based research. Ultimately, our findings demonstrate that SOX2 is not absolutely essential in LUAD cancer cells. This emphasizes the necessity of considering cancer subtype-dependent and context-dependent factors when targeting SOX2 overexpression as a potential therapeutic vulnerability in diverse cancers.